PENENTUAN PERINGKAT SOFT SKILL SISWA MENGGUNAKAN METODE FUZZY TAHANI STUDI KASUS SDN 1 PANDANSARI LOR - Sabilillah Alfath; Fitri Marisa; Indra Dharma Wijaya (STMIK YADIKA BANGIL, 2019)
This research is motivated by observations and research experience, that the process of giving students grades to determine class rankings is still not optimal. Because it is done manually, so it requires a relatively long time. The problem of this study is (1) How to design a decision clipping decision support system for students using the Fuzzy database method with the tahani model? (2) Can using the application help the school to rank students and be faster than manual calculations? This study uses a quantitative research approach where the observations carried out include everything related to the object of research at elementary school Pandansari Lor 1, the phenomena and correlations that exist among them, and presented in the form of numbers. The conclusions of the results of this study are (1) The research succeeded in designing and making a decision support system to rank students' data using the Fuzzy method of the tahani model. (2) The system can rank student grades faster and accurately compared to manual methods. Based on the conclusions of the results of this study, it is recommended: (1) Need to add student data print menus to this application, to make it easier for teachers to score student grades. (2) Ranking can only be done from 1 class. Need to add data to be able to rank different class data.Keywords: decision support system, fuzzy database, tahani model, web.